The Influence of Immersive Commerce and Augmented Reality on Increasing Trust in E-Commerce Transactions - Sekar Farahdila I; Vinsent Brilian A (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the impact of immersive commerce and augmented reality (AR) on consumer trust in e-commerce transactions using secondary industry data from the BrandXR 2025 Research on Augmented Reality in Retail & E-Commerce. Quantitative data was analyzed descriptively to evaluate the adoption rate of immersive technologies (immersive commerce and AR) and their relationship with consumer trust perceptions. The results show that immersive commerce, characterized by interactive and realistic user experiences, has a positive impact on consumer trust. Similarly, AR which offers realistic product visualization, has a significant impact on strengthening consumer trust in purchasing decisions. Simultaneously, the integration of immersive commerce and AR enhance the digital shopping experience, which can reduce risk perception and increase trust in online transactions. These findings empirically contribute to the literature on digital consumer behavior and e-commerce strategies, and suggest that businesses adopt immersive technologies to increase consumer trust and engagement in the online commerce ecosystem.